Error estimates for the finite element solutions of variational inequalities - M. Aslam Noor (International Journal of Mathematics and Mathematical Sciences)
For piecewise linear approximation of variational inequalities associated with the mildly nonlinear elliptic boundary value problems having auxiliary constraint conditions, we prove that the error estimate for u−uh in the W1,2-norm is of order h.